2019
DOI: 10.1029/2018jb017079
|View full text |Cite
|
Sign up to set email alerts
|

Stress Field in the 2016 Kumamoto Earthquake (M 7.3) Area

Abstract: We used 1‐D and 3‐D velocity models to determine focal mechanism solutions (FMSs) of 349 crustal earthquakes (M 2.7–7.3) and stress tensors in the source area of the 2016 Kumamoto earthquake (M 7.3) that occurred on the Futagawa‐Hinagu fault zone in Kyushu, Southwest Japan. There are some differences in the FMSs determined with the 1‐D and 3‐D velocity models. The use of the 3‐D velocity model leads to better results of stress tensors, which are determined by inverting the FMSs. The orientation of the minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Finally, we apply the inversion scheme to estimate the tectonic stress field using the coarse model. The tectonic stress is assumed to be uniaxial tensional because numerous researches have demonstrated that tensional stress with a nearly north‐south orientation is dominant throughout the whole Kyushu island (Matsumoto et al., 2015; Mitsuoka et al., 2020; Savage et al., 2016; Yoshida et al., 2016; Yu et al., 2019). Thus, the parameter m $\boldsymbol{m}$ is composed of the amount and direction of the horizontal minimum compressional stress ( Shmin ${S}_{h\text{min}}$).…”
Section: Results Of the Kumamoto Earthquakementioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we apply the inversion scheme to estimate the tectonic stress field using the coarse model. The tectonic stress is assumed to be uniaxial tensional because numerous researches have demonstrated that tensional stress with a nearly north‐south orientation is dominant throughout the whole Kyushu island (Matsumoto et al., 2015; Mitsuoka et al., 2020; Savage et al., 2016; Yoshida et al., 2016; Yu et al., 2019). Thus, the parameter m $\boldsymbol{m}$ is composed of the amount and direction of the horizontal minimum compressional stress ( Shmin ${S}_{h\text{min}}$).…”
Section: Results Of the Kumamoto Earthquakementioning
confidence: 99%
“…Therefore, based on the inversion result of the uniaxial tectonic stress, we can conclude that 𝐴𝐴 𝐴𝐴3 is horizontal and nearly in the direction of N-S (N6.5°W), and the magnitude of 𝐴𝐴 𝐴𝐴2 is almost equal to that of 𝐴𝐴 𝐴𝐴1 . Yoshida et al (2016) and Yu et al (2019) have investigated the normalized deviatoric stress (orientations and relative magnitudes of the principal stresses) near the source region of the Kumamoto earthquake using large amounts of focal mechanisms based on the Wallace-Bott assumption. They suggested that the 𝐴𝐴 𝐴𝐴3 axis trends NNW-SSE or N-S horizontally, which is the same as our results.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enormous strain energy can be accumulated in the megathrust zone due to the plate convergence along the frictional plate interface, which can intermittently host huge earthquakes with magnitudes up to Mw 9.0 or greater. Due to the existence of strong structural heterogeneities and complex stress field in subduction zones (e.g., Hua et al., 2020; Huang & Zhao, 2013; Yu et al., 2019; Zhao et al., 2011), uneven interplate seismic coupling, segmentation of great megathrust ruptures and heterogeneous distribution of various type earthquakes (e.g., interplate, intraslab, and slow earthquakes, etc.) have been observed in many subduction regions (Chlieh et al., 2008; Hasegawa et al., 2009; Sato et al., 2013; Schmalzle et al., 2014; Sippl et al., 2021; Yokota et al., 2016).…”
Section: Introductionmentioning
confidence: 99%